Fostering Multiculturalism in Indonesian Schools: A Case Study at SMKS Dirgantara Putra Bangsa, Yogyakarta - Juwitaningrum, Yuyun; Hakim, Lukman (Journal International Dakwah and Communication, 2025)
This case study explores the implementation of multiculturalism at SMKS Dirgantara Putra Bangsa, a vocational school in Yogyakarta, Indonesia. Given Indonesia’s rich cultural diversity, educational institutions are vital in fostering intercultural understanding and promoting inclusive values, yet vocational schools often struggle to build genuine cross-cultural understanding among students from diverse backgrounds. Using a qualitative approach, data from interviews with the principal, vice principal of student affairs, and students from outside Java revealed the school employs various socio-cultural communication strategies to aid cultural adaptation and foster mutual respect. These strategies include integrating Javanese cultural practices into daily routines, consistently promoting character values like honesty and discipline, and incorporating cultural arts into the curriculum. The school also encourages student participation in cultural performances and implements the “5S” behavioral initiative—Smile, Greet, Greet Back, Politeness, and Courtesy—collectively nurturing a welcoming and respectful school environment. This study contributes to the growing literature on multicultural education in Southeast Asia and provides a practical model for other schools seeking to create culturally responsive and harmonious learning environments.